IMPULSIVE REACTION MEDIATES SITUATIONAL FACTORS ON IMPULSE BUYING DECISION OF FOOD PRODUCTS IN SUPERMARKETS IN MALANG CITY - Puspaningrum, Astrid (Jurnal Aplikasi Manajemen, 2017)
Retail Business in Indonesia has growth in a great number, especially supermarket, in Malang City, causes the tight competition. The understanding of situational effect on consumer's purchasing decision assists the manager of supermarket to prepare the plan and appropriate retail strategy to deal with such competition. The purpose of this research are (1) to determine the impact of situational factors on impulse buying decisions in Food Product at Giant Supermarket (2) to determine the impact of situational factors on impulse buying decisions through buying impulsiveness in Food Product at Giant Supermarket (3) to determine the impact of buying impulsiveness on impulse buying decisions in Food Product at Giant Supermarket. 140 respondents were taken as sample. Sample method is purposive sampling. Tests a hypothetical model using Path Analysis. The result of this research are (1) situational factors have a significant impact on impulse buying decisions in Food Product at Giant Supermarket (2) situational factors have no significant impact on impulse buying decisions through buying impulsiveness in Food Product at Giant Supermarket (3) buying impulsiveness have no significant impact on impulse buying decisions in Food Product at Giant Supermarket. The research suggest for Giant Supermarket are to make a better exterior and interior so the customer can shop and do recreation at a same time and also to complete the food product such as fruits and always update the new food product in Indonesia.